Aberrant expression of miR-148a-3p in Alzheimer's disease and its protective role against amyloid-β induced neurotoxicity. (21st June 2021) - Zhang, Hao; Liu, Wei; Ge, Hongliang; Li, Kun
Highlights: Serum miR-148a-3p was lower in AD patients. Serum miR-148a-3p was positively associated with the MMSE score in AD patients. MiR-148a-3p serves as promising biomarker for the diagnosis of AD. MiR-148a-3p attenuated Aβinduced neurotoxicity by targeting ROCK1. Abstract: Objective: The current study investigated the expression change and clinical value of miR-148a-3p in AD patients, and further examined the role of miR-148a-3p in Aβ-induced neurotoxicity in SH-SY5Y cells. Material and methods: qRT-PCR was used for the measurement of miR-148a-3p expression levels. ROC curve was established to calculate the diagnostic value of serum miR-148a-3p for AD. CCK-8 and flow cytometry assay was applied for the detection of cell viability and apoptosis. Additionally, the luciferase reporter assay was performed to confirm the target relationship between ROCK1 and miR-148a-3p. Results: Serum miR-148a-3p was downregulated in AD patients compared with that in healthy controls, and was positively associated with the MMSE score in AD patients. Serum miR-148a-3p had the potential to distinguish AD patients from healthy controls, and the diagnostic sensitivity and specificity were respectively 85.5 % and 87.0 % at a cutoff value of 0.827. MiR-148a-3p attenuated Aβ25–35 induced neurotoxicity in SH-SY5Y cells, and ROCK1 was the target gene. Conclusion: Serum miR-148a-3p is correlated with MMSE score in AD patients, and it might be helpful for the AD diagnosis. Overexpression of miR-148a-3p attenuated Aβ induced neurotoxicity in AD by targeting ROCK1.